Perancangan Konsep Pengembangan Buku Ajar Geografi Bermuatan Ketimpangan Ruang pada Jenjang SMA - Farkhan, Muhammad Robith; Maryani, Enok (Universitas Muhammadiyah Magelang, 2026)
The study of spatial inequality as a unique study of the discipline of geography that can be embedded in geography textbooks. Currently, geography textbooks in high schools are considered to still focus on instilling complex scientific concepts and are still not contextual, and there is little encounter of actual problems and understanding of local geography. This is very different when compared to geography textbooks used by students in various countries, referring to